Ephyra-Epirus : the Mycenaean Acropolis : results of the excavations 1975-1986 and 2007-2008 - Papadopoulos, Thanasis J., (Archaeopress Archaeology, 2020)
This volume presents the results of the 1975-1986 and 2007-2008 excavations on the prehistoric-Mycenaean acropolis of Ephyra, one of the most important Bronze Age sites of Epirus. Ephyra is a small coastal fortified site in the region of the lower Acheron valley, and it has produced impressive and, in some cases, unique Bronze Age remains.